AI CHATBOTS IN ELT: EVALUATING THE IMPACT ON SPEAKING SKILL DEVELOPMENT OF HIGHER EDUCATION STUDENTS - Ravshanova Marjona Jumaniyoz qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article discusses the Effectiveness of AI-Powered Chatbots in Developing Speaking Skills of Higher Education Students.This study addresses the perennial challenge of limited speaking practice opportunities in conventional English Language Teaching settings. AI-powered conversational agents (chatbots) have emerged as a promising solution, offering students continuous, personalized practice and automated feedback. The primary aim of this research is to evaluate the effectiveness of integrating AI-chatbots into the English language teaching curriculum for developing the speaking skills of students in higher education institutions in Uzbekistan. A 12-week quasi-experimental study was conducted involving two groups: a control group (traditional instruction) and an experimental group (traditional instruction plus regular AI-chatbot practice). The students’ speaking performance was assessed using pre-tests and post-tests focusing on fluency, accuracy, and lexical richness. The findings indicate that the experimental group demonstrated a statistically significant improvement in speaking skills compared to the control group. Specifically, the use of AI-chatbots positively enhanced students’ fluency and motivation for autonomous learning. The study confirms the pedagogical value of AI-chatbots as an effective tool for teaching English in the Uzbek educational context and provides practical implications for enhancing English language teaching programs through technology integration.